Incidence of Meniere disease in a tertiary healthcare center in Mumbai - Penwal, Suman S.; Valame, Deepa A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The disorder of the inner ear related to abnormally increased levels of endolymph in the membranous labyrinth is called Meniere’s disease. It is well studied that the prevalence of Meniere’s disease varies widely across regions. It was found to be 13% to 42% around the world in various places. It is important to know the incidence in India to know the population suffering and to plan better treatment strategies to cater to rehabilitation strategies. Hence, the current study was planned to estimate a load of Meniere’s disease in a tertiary care hospital in Mumbai. Methods: A retrospective analysis of the case reports was undertaken. As per American academy of otolaryngology-head and neck surgery (AAO-HNS, 2020), the patients were separated as definite and probable Meniere’s disease. Results: The descriptive analysis revealed that 6 in 1000 patients reporting for hearing evaluation in a tertiary care hospital are suffering from Meniere’s disease. There was a female preponderance found in the patients with a gender ratio of 1.85:1. Conclusions: The incidence of Meniere’s disease in a tertiary care hospital in Mumbai was found to be 0.61% of all the patients tested for hearing impairment.